Effect of solvent-induced packing transitions on N-capped diphenylalanine peptide crystal growth - Yoav Dan; Zohar A. Arnon; Yiming Tang; Mathar Kravikass; Yun Zhou; Rajkumar Misra; Om Shanker Tiwari; Linda J. W. Shimon; Roy Beck; Ehud Gazit; Guanghong Wei; Lihi Adler-Abramovich (Nature Communications)
Abstract Self-assembled supramolecular materials have gained extensive interest due to their ability to form structures with diverse physical, chemical, and biological properties. These characteristics arise from the precise arrangement of building blocks at the nanoscale. There is an unmet need to efficiently manipulate crystalline materials’ solid-state packing and monitor the effect on growth at a single crystal level. Herein, we used N-capped diphenylalanine peptide module to study the conditions affecting lattice configuration. In addition to the canonical monoclinic crystal, we found the peptide to alternatively assemble into an orthorhombic crystalline form. Wide-angle X-ray analysis indicated that the sharp transition between the distinct crystalline polymorphic forms depends on solvent composition, indicating the impact of the immediate molecular milieu on the monomeric conformation and the interactions with crystals. Both experimental and molecular dynamics simulations corroborate the results and demonstrate that solution composition directs the monomers to adopt specific conformations and affects their interactions with pre-formed crystal templates, resulting in either crystal growth, steady-state, or disassembly. These notions provide a profound understanding of crystal polymorphism and growth mechanisms at the molecular level, enabling the advanced design of bio-inspired materials.